2008
DOI: 10.1016/j.virusres.2007.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Interferon β1-a and selective anti-5HT2a receptor antagonists inhibit infection of human glial cells by JC virus

Abstract: JC virus (JCV) is the causative agent of progressive multifocal leukoenchaphalopathy (PML). The disease develops when JCV gains access to the central nervous system, infects and destroys oligodendrocytes. The disease is rapidly progressing, typically fatal and no effective therapies exist to treat or prevent PML. The recent occurrence of PML in multiple sclerosis patients being treated with Avonex (IFNβ1a) and Tysabri (Natalizumab) and the recent reports linking JCV infection to the 5HT 2a serotonin receptor l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
37
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 35 publications
5
37
0
1
Order By: Relevance
“…3). This level of reduction is similar to what is seen when these low doses of antagonists are used on SVG-A cells (6,18). The hESC-derived OPCs were more prone to drug toxicity than the established SVG-A cell line was, and higher doses of drug could not be used reliably on these cells.…”
supporting
confidence: 70%
“…3). This level of reduction is similar to what is seen when these low doses of antagonists are used on SVG-A cells (6,18). The hESC-derived OPCs were more prone to drug toxicity than the established SVG-A cell line was, and higher doses of drug could not be used reliably on these cells.…”
supporting
confidence: 70%
“…As these drugs antagonize both serotonin and dopamine receptors, it was hypothesized that one or both of these neurotransmitter receptors might function as a virus receptor on glial cells. Subsequent studies using drugs that specifically antagonized dopamine or serotonin receptors suggested that the 5HT 2A subtype of the serotonin receptor functioned as a JCV receptor (130,373). It was then shown that expression of the 5HT 2A receptor was sufficient to allow viral entry to cells lacking this receptor (HeLa and HEK293A) and that antibodies to the 5HT 2A R blocked infection (130,296).…”
Section: Virus Receptorsmentioning
confidence: 99%
“…More recent studies have focused on blocking JCV binding to 5HT 2A R on permissive cells in the brain using serotonin receptor agonists (385). Blocking access to 5HT 2A R using antibodies or the serotonin receptor agonists chlorpromazine and clozapine was effective in limiting JCV infection in human brain-derived cell cultures (21,30,130,371,373,442); however, these drugs have serious side effects and toxicity issues. Newer antipsychotics, including zisprasidone, risperidone, and olanzapine, were shown to inhibit JCV infection up to 10-fold more potently than the previously studied agonists in an in vitro system (11).…”
Section: Treatment Of Pml and Pml-irismentioning
confidence: 99%
“…Conversely, it has been reported that JCPyV infection can occur in the absence of 5-HT 2A R in human brain microvascular endothelial cells (36). Moreover, pretreatment of glial cells with the specific 5-HT 2 receptor inhibitors ritanserin, ketanserin, mianserin, and mirtazapine significantly reduce JCPyV infection (34,(37)(38)(39)(40)(41). In the clinical setting, mirtazapine has been administered to indi-viduals diagnosed with PML, either alone or in combination with other drugs, and in several cases, it has been shown to delay the progression of this fatal disease when given at the onset of PML symptoms (42)(43)(44)(45).…”
mentioning
confidence: 98%